Skipping Breakfast Is Associated with Hypertension in Adults: A Meta-Analysis - Zishuo Li; Hongli Li; Qin Xu; Yanli Long (International Journal of Hypertension)
Previous studies evaluating the association between skipping breakfast and hypertension in adult population showed inconsistent results. We performed a meta-analysis to systematically evaluate the association. Observational studies which evaluated the relationship between skipping breakfast and hypertension in adult population with multivariate analyses were identified by systematic search of PubMed, Embase, and Web of Science databases. A random-effect model which incorporated the potential intrastudy heterogeneity was used for the meta-analysis. A total of six observational studies with 14189 adults were included, and 3577 of them were breakfast skippers. Pooled results showed that skipping breakfast was independently associated with hypertension in these populations (adjusted odds ratio (OR): 1.20, 95% confidence interval: 1.08 to 1.33, P<0.001) with no significant heterogeneity (I2 = 0%). Sensitivity by excluding one study at a time showed consistent results (OR: 1.18 to 1.22, all P <0.01). Subgroup analyses showed that the association between skipping breakfast and hypertension in adults was consistent in the general population and in patients with type 2 diabetes, in studies from different countries, in cohort and cross-sectional studies, in breakfast skippers defined as taking breakfast ≤3 days/week and as self-reported habitual breakfast skipping, and in studies with and without adjustment of body mass index (Pfor subgroup difference, all P>0.10). In conclusion, skipping breakfast is associated with hypertension in the adult population.